Categorization principles of modal meaning categories: a critical assessment - Ilse Depraetere (Anglophonia)
This paper offers a critical analysis of the features used to define categories of modal meaning (expressed by modal verbs). First, Palmer’s (1990) and Huddleston and Pullum et al’s (2002) definition of dynamic modality is compared with the taxonomic approach to that area of modal meaning in Depraetere and Reed (2011) and Depraetere (2014). The next part of the paper is focussed on the ways in which deontic necessity is defined in Huddleston and Pullum et al (2002), Van der Auwera and Plungian (1998), Coates (1983). Finally, the defining features of the category of dynamic implication are analysed. The discussion is meant to make explicit and assess the diverse strategies used to delineate categories of modal meaning. Some principles of methodological good practice are put forward.